Which Children with Autism Spectrum Disorder Have Abnormal Brain MRI Findings? Clinical Correlates in a 1884-Patient Cohort - Viswabhaskar Susarla; Mariah George; Ananthi Rathinam; Danish Bhatti (Neurology International, 2026)
Background: Brain MRI in patients with autism spectrum disorder (ASD) is generally considered when additional neurologic, developmental, or syndromic concerns warrant structural evaluation. In the study practice, ASD alone was not used as the reason to obtain MRI. We examined documented MRI use and broad result coding while explicitly separating selection for imaging from abnormal-result status. Methods: This retrospective specialty-practice cohort included 1884 patients with ASD. The primary outcome was the proportion of documented MRI examinations coded abnormal. Secondary analyses examined associations of age, sex, seizure history, EEG status, and genetic test status with abnormal versus normal MRI coding and with documented MRI utilization. MRI categories and the pediatric restriction were exploratory and sensitivity analyses. Results: An MRI result was recorded for 704 patients (37.4%; 95% CI 35.2–39.6); 322 were coded abnormal (45.7%; 95% CI 42.0–49.5). The abnormal-result models had low in-sample discrimination (AUC 0.528 and 0.553), and adjusted confidence intervals for all measured variables included 1.00; these results do not demonstrate equivalence between clinical groups. Seizure history was associated with documented imaging in the full cohort (aOR 2.47, 95% CI 1.94–3.14), and abnormal EEG was associated in the exploratory complete-case utilization model (aOR 2.83, 95% CI 1.93–4.14). Conclusions: Broad MRI abnormalities were frequent among patients selected for imaging because of additional clinical concerns, but a broad abnormal code is not equivalent to clinically actionable yield. The routinely captured variables available in this dataset were insufficient to distinguish abnormal from normal MRI coding. These findings favor individualized MRI decisions based on the clinical question prompting imaging and motivate future studies with richer neurologic and developmental phenotyping.